A step in the right direction: identifying strategies for preparing initial teacher candidates for culturally diverse classrooms in Baden-Württemberg - Igboegwu, Amarachi Adannaya (2022)
In a bid to prepare initial teacher candidates for culturally diverse classrooms, this research study examined effective strategies for equipping initial teacher candidates for culturally diverse classrooms. This research study implemented a qualitative case study design to determine teaching strategies that prepare initial teacher candidates for culturally diverse classrooms. With guidance from extant literature on initial teacher candidate training as well as interviews with teacher educators, I designed a seminar that focused on helping students interrogate their beliefs and values as they pertain to teaching culturally diverse classrooms. Expert interviews were conducted to gain deeper insights into how pre-service training programmes can be further developed. Given that the study was also focused on initial teacher candidates, the seminar Teaching Consciously in Culturally Diverse Classrooms, provided rich data for understanding how the students responded to modules and ensuing class interactions. Data collected from students on the Culturally Responsive Classroom Management Self-Efficacy (CRCMSE) survey demonstrate that participants felt more self-confident applying culturally responsive classroom management strategies after taking the eight-week seminar intervention. Furthermore, knowledge gaps highlighted by anti-bias experts in traditional initial teacher training programmes illuminate why initial teacher candidates are still unprepared for culturally diverse classrooms. Underscoring the need for a transformative approach to initial-teacher training, this study proposes ideological and strategic considerations for a renewed approach to conducting initial teacher training and recommends modular courses for adaptation and incorporation in future initial teacher training programmes.